The Social marginalization and its relationship with the Subversive personality - Al-Abidy, Adel Khudhair Ubais (Al-Adab Journal, 2020)
The research aims Measure .the Social marginalization and the destructiveness personality. To Defining the differences in the Social margianalization and destructiveness personality according to gendar (males & females ) besides to identifying the correlation between Social margianalization and destructiveness personality, In order to accomplish thr researchs aims, the researcher adoption Al-Shammari.2013 scale which consisted of (28) paragraphs to destructiveness personality , and Gallie scale ,2002 which was translated by Al-Janabi,2014 which consisting of (19) paragraphs Social marginalization acheived the validity and the ability and psychometric devices, the two Measures where applied to sample amounted to (200) students "males & females"The data where statistically processed , and the results concluded that evening studies Students they suffer from the. Social marginalization and destructiveness personality-and There are differences in the destructiveness personality between males and females and in favor of males,while there are no differences in the Social marginalization .Moreover, there is a correlation between the Social marginalization and subversive personality. In light of the results, the researcher set of recomendations and suggestions.